Gamma Radiation-Induced Synthesis of Carboxymethyl Cellulose-Acrylic Acid Hydrogels for Methylene Blue Dye Removal - Sabuj Chandra Sutradhar; Nipa Banik; Mobinul Islam; Mohammad Mizanur Rahman Khan; Jae-Ho Jeong (Gels)
This study aims to develop efficient and sustainable hydrogels for dye adsorption, addressing the critical need for improved wastewater treatment methods. Carboxymethyl cellulose (CMC)-based hydrogels grafted with AAc were synthesized using gamma radiation polymerization. Various AAc to CMC ratios (5:5, 5:7.5, 5:10, 5:15) were treated with 37% NaOH and exposed to 1–15 kGy radiation, with the optimal hydrogel obtained at 5 kGy. Swelling studies showed an increase in swelling with 5–7.5% AAc content, with the 5:7.5 hydrogel achieving the highest swelling at 18,774.60 (g/g). FTIR spectroscopy confirmed the interaction between AAc and CMC, indicating the successful formation of the hydrogel. DSC analysis revealed that higher AAc content led to increased glass transition and decomposition temperatures, thereby enhancing thermal stability. The swelling kinetics were linked to a reduction in pore size and improved AAc grafting. The 5:7.5 hydrogel demonstrated the highest adsorption capacity (681 mg/g) for methylene blue at 80 mg/L, achieving a desorption efficiency of 95% in 2M HCl. Kinetic analysis revealed non-uniform physisorption on a heterogeneous surface, which followed Schott’s pseudo-second-order model. This study advances the development of efficient hydrogels for water purification, providing a cost-effective and environmentally friendly solution for large-scale applications.